Metabolic modulation and multi-species interaction: Lactiplantibacillus plantarum’s impact on Streptococcus mutans-Candida albicans in a mucosal model - Li, Ting; Wu, Yan; Zhang, Lanxin; Alyami, Hiba; Alomeir, Nora; Wu, Tongtong; Xiao, Jin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionStreptococcus mutans and Candida albicans are key pathogens in dental caries and oral candidiasis. While Lactiplantibacillus plantarum and the prebiotic galactooligosaccharides (GOS) have been shown to inhibit these pathogens and their interactions in biofilm and planktonic models, their effects and mechanisms in an oral mucosal context remain unclear.MethodsThis study investigated the impact of L. plantarum, alone and in combination with GOS, using an oral mucosal model. The analyses focused on pathogen viability, adhesion, transmigration, virulence expression, mucosal barrier integrity, inflammatory response, extracellular polysaccharide production, and metabolism.ResultsL. plantarum reduced the viability of S. mutans, inhibited the adhesion of both pathogens to the oral mucosa, and decreased the transmigration of S. mutans through the mucosal membrane. It also attenuated the virulence of C. albicans by inhibiting hyphae formation and gene expression. Furthermore, L. plantarum helped maintain mucosal barrier integrity by mitigating the epithelial inflammatory response induced by the pathogens. The combination of GOS and L. plantarum significantly reduced pathogenic extracellular polysaccharide production by S. mutans, creating a metabolic microenvironment less conducive to the survival and interaction of both pathogens. Notably, L. plantarum significantly altered the metabolic landscape of these pathogens, especially under GOS conditions.DiscussionThese findings demonstrate that L. plantarum, particularly when combined with GOS, exerts inhibitory effects on S. mutans and C. albicans in an oral mucosal model through metabolic and immunologic regulation. The results highlight the potential of synbiotic strategies (probiotics and prebiotics) for preventing and mitigating oral diseases involving the mucosal barrier and the pathogenesis of S. mutans and C. albicans.